Study the Effects of (8-oxo-Guanine DNA Glycosylase 1 rs1052133) Polymorphism on Gene Expression as a Predisposing Factor for DNA Mutation in Midland Refineries Company-Dura Refinery Workers (Iraqi Journal of Medical Sciences, 2022)
Background: Refineries are exposed to different types of air pollutants, among them, polycyclic aromatic hydrocarbons (PAHs), they are a group of over hundred different kinds of hazardous organic chemicals (pollutants), which are formed primarily during the incomplete burning of oil, gas and coal. PAHs are metabolized in different organs of human body especially in the liver leading to generation of mutagenic metabolites, of them, the reactive oxygen species, which damage DNA by binding with guanine base leading to formation of 8-hydroxyguanine. The 8-oxo-guanine DNA glycosylase (hOGG1 rs1052133) gene, is a regulatory gene binds with 8-oxo-DG in the DNA to initiate base excision repair (BER) pathway.Objective: To investigate the role of (hOGG1 rs1052133) gene polymorphism in single nucleotide polymorphism repair.Methods: One hundred sixty-eight (168) subjects were participated in this study. They were they divided into three groups (country side, office workers and field workers). PAHs were analyzed in all participant by Gas Chromatography Coupled with a Mass Spectrophotometry GC/MS. SNP for hOGG1 and gene expression were detecting by real time polymerase chain reaction and quantitative polymerase chain reaction for each subject respectively.Results: PAH were detected in blood serum of refineries workers and not detected in country side participants. The level of hOGG1 gene expression was higher in GG genotype than GC and CC genotype.Conclusion: Refineries worker are at high risk of developing malignant transformation and serious disease due to high level of PAH compared to other population. hOGG1 plays an important role in DNA repair following DNA mutation.Keywords: Poly cyclic aromatic hydrocarbons, HOGGI, gene expressionCitation: Al-Ani RH, Al-Wasiti EA, Shukur AS. Study the Effects of (8-oxo-Guanine DNA Glycosylase 1 rs1052133) Polymorphism on Gene Expression as a Predisposing Factor for DNA Mutation in Midland Refineries Company-Dura Refinery Workers. Iraqi JMS. 2022; 20(1): 90-97. doi: 10.22578/IJMS.20.1.12
Keywords: Poly cyclic aromatic hydrocarbons; HOGGI; gene expression